2012
DOI: 10.1007/s00401-012-0957-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel pathways involved in the pathogenesis of human adamantinomatous craniopharyngioma

Abstract: Activating mutations in the gene encoding β-catenin have been identified in the paediatric form of human craniopharyngioma (adamantinomatous craniopharyngioma, ACP), a histologically benign but aggressive pituitary tumour accounting for up to 10% of paediatric intracranial tumours. Recently, we generated an ACP mouse model and revealed that, as in human ACP, nucleocytoplasmic accumulation of β-catenin (β-catnc) and over-activation of the Wnt/β-catenin pathway occurs only in a very small proportion of cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
196
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(215 citation statements)
references
References 63 publications
14
196
0
5
Order By: Relevance
“…Such assumption is strengthened by the detection of a side population in human pituitary adenomas that could represent tumor-initiating cells due to the expression of multidrug transporters, oncogenes and components of several stem cell pathways (Vankelecom & Gremeaux 2010). Moreover, craniopharyngiomas arising from embryonic pituitary tissue were found to express the stem cell markers SOX2, SOX9, OCT4, KLF4 and b-catenin (Gaston-Massuet et al 2011, Andoniadou et al 2012, Garcia-Lavandeira et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Such assumption is strengthened by the detection of a side population in human pituitary adenomas that could represent tumor-initiating cells due to the expression of multidrug transporters, oncogenes and components of several stem cell pathways (Vankelecom & Gremeaux 2010). Moreover, craniopharyngiomas arising from embryonic pituitary tissue were found to express the stem cell markers SOX2, SOX9, OCT4, KLF4 and b-catenin (Gaston-Massuet et al 2011, Andoniadou et al 2012, Garcia-Lavandeira et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Through isolating the cluster cells and performing gene expression analyses, we identified that they expressed a vast array of growth factors, chemokines and cytokines including members of the TGF, FGF and PDGF families of growth factors among many others. These cells could therefore act as signalling centres, likely changing the microenvironment and facilitating tumorigenesis (Andoniadou et al 2012(Andoniadou et al , 2013). An observation that was indicative of the potential of these cluster cells was that actively proliferating cells, as marked by immunofluorescence of Ki67, were readily detected in close proximity to the cell clusters in both mouse and human ACP (Gaston-Massuet et al 2011).…”
Section: Stem Cells and Pituitary Tumoursmentioning
confidence: 99%
“…In the adherent cultures, time-lapse imaging of singe cells plated at clonal density confirmed that they gave rise to single colonies that contained multiple EYFP-positive cells, demonstrating self-renewal. Withdrawal of growth factors and prolonged culture in differentiation conditions promoted the expression of markers of the three main pituitary lineages and the expression of differentiation markers, as detected by qPCR (Andoniadou et al 2012). Interestingly, only a small percentage of SOX2 + cells were able to form colonies (up to 5 % depending on age), possibly reflecting heterogeneity within this population in terms of their potential; alternatively, the culture requirements allowed for expansion of a restricted subset of cells, where more cell types could have self-renewal capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations